Role of casein kinase 1 in the amoeboid migration of B-cell leukemic and lymphoma cells: A quantitative live imaging in the confined environment - Čada, Štěpán; Vondálová Blanářová, Olga; Gömoryová, Kristína; Mikulová, Antónia; Bačovská, Petra; Zezula, Nikodém; Kumari Jadaun, Alka; Janovská, Pavlína; Plešingerová, Hana; Bryja, Vítězslav (Frontiers in Cell and Developmental Biology, 2022)
Migratory properties of leukemic cells are commonly associated with their pathological potential and can significantly affect the disease progression. While the research in immunopathology mostly employed powerful indirect methods such as flow cytometry, these cells were rarely observed directly using live imaging microscopy. This is especially true for the malignant cells of B-cell lineage, such as those originating from chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL). In this study we employed open-source image analysis tools to automatically and quantitively describe the amoeboid migration of four B-cell leukemic and lymphoma cell lines as well as primary CLL cells. To avoid the effect of shear stress of medium on these usually non-adherent cells, we have confined the cells using a modified under-agarose assay. Surprisingly, behavior of tested cell lines differed substantially - in terms of basal motility or response to chemokines and VCAM1 stimulation. Since casein kinase 1 (CK1) was reported as a regulator of B cell migration and a promoter of CLL, we looked at the effects of CK1 inhibition in more detail. Migration analysis revealed that CK1 inhibition induced rapid negative effects on migratory polarity of these cells, which was quantitatively and morphologically distinct from the effect of ROCK inhibition. We have set up an assay that visualizes endocytic vesicles in the uropod and facilitates morphological analysis. This assay hints that the effect of CK1 inhibition might be connected to defects of polarized intracellular transport. In summary, (i) we introduce and validate pipeline for the imaging and quantitative assessment of the amoeboid migration of CLL/MCL cells, (ii) provide evidence that the assay is sensitive enough to mechanistically study migration defects identified by transwell assay, and (iii) describe the polarity defects induced by inhibition or deletion of CK1ε.